Performance Evaluation of RIPng, EIGRPv6 and OSPFv3 for Real Time Applications (Journal of Engineering, 2018)
In this modern Internet era and the transition to IPv6, routing protocols must adjust to assist this transformation. RIPng, EIGRPv6 and OSPFv3 are the dominant IPv6 IGRP (Interior Gateway Routing Protocols). Selecting the best routing protocol among the available is a critical task, which depends upon the network requirement and performance parameters of different real time applications. The primary motivation of this paper is to estimate the performance of these protocols in real time applications. The evaluation is based on a number of criteria including:  network convergence duration, Http Page Response Time, DB Query Response Time, IPv6 traffic dropped, video packet delay variation and video packet end to end delay.  After examining the simulation results, a conclusion will be extracted to reveal the findings of which protocol performs the best upon implementation within a IPv6 WAN. OPNET modeler simulator is used to evaluate the accomplishment of these protocols. To get the results, three scenarios are designed, one for each protocol.